Investigating the ASMR Afterglow: Post-Exposure Emotional and Physiological Responses - Dhanji, Urvi (Auckland University of Technology, 2026)
Autonomous Sensory Meridian Response (ASMR) is a sensory experience in which specific auditory or audiovisual triggers, such as whispering, tapping, or gentle, repetitive sounds, elicit a tingling sensation along the scalp and spine, often accompanied by feelings of relaxation and pleasure. ASMR has been linked to increased relaxation and reduced physiological activation during exposure. To date, limited research has investigated the short-term persistence of ASMR-related emotional and perceived physiological responses following exposure. Understanding these post-exposure effects may provide a preliminary foundation for future marketing and consumer research. This study addresses this by investigating whether ASMR produces measurable post-exposure changes in self-reported emotional and physiological responses over short time intervals. Understanding how long ASMR effects last is a necessary first step before considering whether it could meaningfully influence consumer experiences. Using a one-condition within-subject, repeated-measures experimental design, 25 participants listened to a five-minute ASMR audio clip in a controlled university classroom at Auckland University of Technology. Self-reported emotional and physiological responses were assessed at 1, 5, and 10 minutes post-exposure using an adapted version of the Pleasure-Arousal-Dominance (PAD) scale and an adapted version of the Relaxation State Questionnaire (RSQ) items. Repeated-measures ANOVA and ANCOVA were conducted to examine temporal changes in ASMR across individual responses, whilst also accounting for potential influences of stress, caffeine intake, and sleep, as these factors are known to affect emotional and physiological states. Findings indicated that pleasure peaked immediately after exposure and declined slightly over time, while arousal and all self-reported physiological measures except sleep, which showed a modest increase, remained stable. This suggests that ASMR produces a brief emotional shift rather than sustained self-reported physiological change. The study contributes to knowledge by extending ASMR research beyond in-stimulus effects and conceptually positions ASMR within the Stimulus-Organism-Response framework, highlighting its relevance to consumer affective processes. From a managerial and consumer perspective, the findings indicate that ASMR may serve as a short-term mood-regulating stimulus, suggesting that low-arousal sensory cues like ASMR could influence how consumers feel in retail environments.